The effect of Translation Memory tools in translated Web texts: Evidence from a comparative product-based study - Jiménez-Crespo, Miguel A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Translation Memory tools have been widely promoted in terms of increased productivity, quality and consistency, while translation scholars have ar-gued that in some cases they might produce the opposite effect. This paper investigates these two related claims through a corpus-based contrastive analysis of 40,000 original and localized Web pages in Spanish. Given that all Web texts are localized using TM tools, the claim of increased quality and consistency is analyzed in contrast with Web texts spontaneously pro-duced in Spanish. The results of the contrastive analysis indicate that local-ized texts tend to replicate source text structures and show higher numbers of inconsistencies at the lexical, syntactic and typographic levels than non-translated Web sites. These findings are associated with lower levels of quality in localized texts as compared to non-translated or spontaneously produced texts.